Transformational Leadership Influence on Innovation Directly and Indirectly through Affective Commitment in Hotel Industry of Malaysia - Shah, Syed Haider Ali; Sultana, Afshan; Gul, Ambreen; Sajjad, Shakeel; Aziz, Shahab; Basit, Abdul; Qadir, Abdullah (International Review of Management and Marketing, 2020)
In order to be innovative in hospitality industry the role of leadership style on employees is very crucial. Leaders are in direct contact with employees and their encouragement and support can trigger the employees to be innovative in delivering the service. In hospitality industry the front-line employees need utmost attention as this industry totally depends on the service of employees especially front-line employees who set the first impression of the hotels. Leadership styles have significant impact on employees' innovation. The study aim was to examine the impact transformational leadership (TL) on innovation in hotel industry of Malaysia. This study filled the gap by examining the transformational leadership style impact on innovation in front line employees. Total 480 questionnaires were distributed among the employees of 5stars hotels which were located in Kuala Lumpur, Malaysia. To examine the hypotheses, this study applied the SEM (AMOS). Findings revealed that transformational leadership had a significant positive effect on employees' innovation. Interesting finding came in mediation analysis, in which affective commitment mediated the relationship between transformational leadership and innovation. Findings of this study are beneficial for management of hotels to understand the role of transformational leadership style, affective commitment on employees in order to be innovative in delivering services. This study provided the in depth analysis for top management to better handle and incite the innovation in employees as the leaders are directly responsible to lead employees in innovative way to be innovative. Keywords: Transformational Leadership, Innovation, Affective commitment, SEM. JEL Classifications: H12; A12 DOI: https://doi.org/10.32479/irmm.10761